Chemical Composition and Antimicrobial Activity of a New Olive Pomace Functional Ingredient - Maria Antónia Nunes; Josman Dantas Palmeira; Diana Melo; Susana Machado; Joana Correia Lobo; Anabela Sílvia Guedes Costa; Rita Carneiro Alves; Helena Ferreira; Maria Beatriz Prior Pinto Oliveira (MDPI AG, 2021)
Olive pomace, an olive oil processing byproduct, can be upcycled and meet the current demand for natural and sustainable food ingredients. In this work, a patented process was used to obtain a functional ingredient from different olive pomaces. The nutritional, chemical and antioxidant profiles, as well as the antimicrobial activity against S. aureus, E. coli and C. albicans, were investigated for the first time. The amount of phenolics ranged between 3.1 and 3.8 g gallic acid eq./100 g in all samples and flavonoids between 2.0 and 3.2 g catechin eq/100 g. No significant differences were found regarding the antioxidant activity. The total fat varied between 5 and 11%, α-tocopherol being the major vitamer and oleic acid the main fatty acid. The protein and ash contents were 1-4% and 10-17%, respectively. The functional ingredient with a higher hydroxytyrosol content (220 mg/100 g) also presented the best minimal inhibitory concentration against the tested bacteria. No activity against C. albicans was verified. This new functional ingredient presents the potential to be used as a natural preservative or as a nutritional profile enhancer. Moreover, it can be an advantageous ingredient in food products, since it comprises specific lipid and hydrophilic bioactive compounds usually not present in other plant extracts.